Berberine Improves Vascular Dysfunction by Inhibiting Trimethylamine-N-oxide via Regulating the Gut Microbiota in Angiotensin II-Induced Hypertensive Mice - Wang, Zhichao; Wu, Fang; Zhou, Qianbing; Qiu, Yumin; Zhang, Jianning; Tu, Qiang; Zhou, Zhe; Shao, Yijia; Xu, Shiyue; Wang, Yan; Tao, Jun (Frontiers in Microbiology, 2022)
Berberine (BBR) has been demonstrated to exert cardiovascular protective effects by regulating gut microbiota. However, few studies examine the effect of BBR on the gut microbiota in hypertension. This study aims to investigate the role of BBR in regulating microbial alterations and vascular function in hypertension. C57BL/6 J mice were infused with Ang II (0.8 mg/kg/day) via osmotic minipumps and treated with BBR (150 mg/kg/day) or choline (1%) for 4 weeks. Blood pressure was detected by tail-cuff measurement once a week. Abdominal aorta pulse wave velocity (PWV) and endothelium dependent vasodilatation were measured to evaluate vascular function. Vascular remodeling was assessed by histological staining of aortic tissue. The fecal microbiota was profiled using 16S ribosomal DNA (rDNA) sequencing. Plasma trimethylamine (TMA)/trimethylamine-N-oxide (TMAO) and hepatic FMO3 expression were measured. We found that BBR treatment significantly alleviated the elevated blood pressure, vascular dysfunction, and pathological remodeling in Ang II-induced hypertensive mice, while choline treatment aggravated hypertension-related vascular dysfunction. 16S rDNA gene sequencing results showed that BBR treatment altered gut microbiota composition (reduced the Firmicutes/Bacteroidetes (F/B) ratio and increased the abundances of Lactobacillus). Moreover, BBR inhibited FMO3 expression and plasma TMA/TMAO production in hypertensive mice. TMAO treatment increased the apoptosis and oxidative stress of human aortic endothelial cells (HAECs) and aggravated Ang II-induced HAECs dysfunction in vitro. These results indicate that the protective effect of BBR in hypertension might be attributed (at least partially) to the inhibition of TMAO production via regulating the gut microbiota.